Alisol A 24-acetate stimulates lipolysis in 3 T3-L1 adipocytes - Hai-xia Lou; Wen-cheng Fu; Jia-xiang Chen; Tian-tian Li; Ying-ying Jiang; Chun-hui Liu; Wen Zhang (BMC, 2021)
Abstract Background Alisol A 24-acetate (AA-24-a), one of the main active triterpenes isolated from the well-known medicinal plant Alisma orientale (Sam.) Juz., exhibits multiple biological activities including hypolipidemic activity. However, its effect on lipid metabolism in adipocytes remains unclear. The present study aimed to clarify the effect of AA-24-a on adipocyte lipolysis and to determine its potential mechanism of action using 3 T3-L1 cells. Methods We assayed the release of glycerol into culture medium of 3 T3-L1 cells under treatment with AA-24-a. Protein and mRNA expression and phosphorylation levels of the main lipases and kinases involved in lipolysis regulation were determined by quantitative polymerase chain reaction and western blotting. Specific inhibitors of protein kinase A (PKA; H89) and extracellular signal-regulated kinase (ERK; PD98059), which are key enzymes in relevant signaling pathways, were used to examine their roles in AA-24-a-stimulated lipolysis. Results AA-24-a significantly stimulated neutral lipolysis in fully differentiated adipocytes. To determine the underlying mechanism, we assessed the changes in mRNA and protein levels of key lipolysis-related genes in the presence or absence of H89 and PD98059. Both inhibitors reduced AA-24-a-induced lipolysis. Moreover, pretreatment with H89 attenuated AA-24-a-induced phosphorylation of hormone-sensitive lipase at Ser660, while pretreatment with PD98059 attenuated AA-24-a-induced downregulation of peroxisome proliferator-activated receptor-γ and perilipin A. Conclusions Our results indicate that AA-24-a promoted neutral lipolysis in 3 T3-L1 adipocytes by activating PKA-mediated phosphorylation of hormone-sensitive lipase and ERK- mediated downregulation of expression of perilipin A.